Diagnostic Accuracy of Serological Markers in Viral Hepatitis and Non Alcoholic Fatty Liver Disease. A Comparative Study in Tertiary Care Hospital of Western Nepal - Mittal, Ankush; Sathian, Brijesh; Chandrasekharan, Nishida; Lekhi, Akshay; Farooqui, Shamim Mohammad; Pandey, Naresh (Nepal Journal of Epidemiology, 2011)
Background: Liver diseases is apparently increasing and emerging as a major public health problem. Worldwide, chronic hepatitis B has become the tenth leading cause of death and persons infected with chronic hepatitis B virus (HBV) and hepatitis C virus (HCV), are about 350 million and 125 million respectively. The aim of current retrospective comparative study was concerned primarily to evaluate the significance of non invasive serological markers for diagnosing liver diseases and their predictive implications in Pokhara valley. Materials and Methods: It was a hospital based retrospective study carried out using the data maintained in the Department of Biochemistry of the Manipal Teaching Hospital, Pokhara, Nepal between 1st June 2009 and 31st October 2010. The variables collected were total protein, albumin, AST, ALT, total bilirubin, direct bilirubin. Descriptive statistics and testing of hypothesis were used for the analysis. Data was analyzed using EPI INFO and SPSS 16 software. Results: Of 515 subjects, 120 were suffering from viral hepatitis and 88 had non alcoholic fatty liver disease. In cases of viral hepatitis, mean values of AST (CI 730.65 to 902.68) and ALT (CI 648.14 to 847.59) were markedly increased as compared to controls. Mild to moderate elevations in serum levels of aspartate aminotransferase (CI 43.42 to 49.49), alanine aminotransferase (CI 43.90 to 53.92) were the most common laboratory abnormalities found in patients with nonalcoholic fatty liver disease. Conclusion: Non invasive tests have demonstrated a reasonable ability to identify significant fibrosis, cirrhosis in particular, nor is it surprising that liver disease specialists and patients favour a non invasive approach. Key words: Viral hepatitis; Nonalcoholic fatty liver disease; Nepal. DOI: http://dx.doi.org/10.3126/nje.v1i2.5137 Nepal Journal of Epidemiology 2011;1 (2):60-63